Planning methods for secure islanding - Nakiganda, Agnes M.; Aristidou, Petros (My University, 2024)
Traditionally, distribution grids have been modelled as either passive elements or aggregated loads, due to their lack of participation in power, frequency, and voltage control. With major transformations in the design and operation of the low-voltage (LV) and medium-voltage (MV) distribution networks (DNs) including the proliferation of distributed energy resources (DERs) and the requirement for them to provide active support to the power grid, DNs are now active. Microgrids (MGs) present a revolutionary step in the electric power system infrastructure designed as independent power distribution networks with the ability to split from the bulk network and form self-sufficient islands.
Intended and Unintended Islanding of Distribution Grids
Keywords: electric power system